Jasmonic acid/methyl jasmonate accumulate in wounded soybean hypocotyls and modulate wound gene expression. - Creelman, R A (1992)
Jasmonic acid (JA) and its methyl ester, methyl jasmonate (MeJA), are plant lipid derivatives that resemble mammalian eicosanoids in structure and biosynthesis. These compounds are proposed to play a role in plant wound and pathogen responses. Here we report the quantitative determination of JA/MeJA in planta by a procedure based on the use of [13C,2H3]MeJA as an internal standard. Wounded soybean (Glycine max [L] Merr. cv. Williams) stems rapidly accumulated MeJA and JA. Addition of MeJA to soybean suspension cultures also increased mRNA levels for three wound-responsive genes (chalcone synthase, vegetative storage protein, and proline-rich cell wall protein) suggesting a role for MeJA/JA in the mediation of several changes in gene expression associated with the plants' response to wounding.